M6A Classification Combined With Tumor Microenvironment Immune Characteristics Analysis of Bladder Cancer - Zhu, Huili; Jia, Xiaocan; Wang, Yuping; Song, Zhijuan; Wang, Nana; Yang, Yongli; Shi, Xuezhong (Frontiers in Oncology, 2021)
Background: Studies have shown N6-methyl adenosine (m6A) plays an important role in cancer progression; however, the underlying mechanism of m6A modification in tumor microenvironment (TME) cell infiltration of bladder cancer remains unclear. This study aimed to investigate the role of m6A modification in TME cell infiltration of bladder cancer. Methods: RNA expression profile and clinical data of bladder cancer were obtained from The Cancer Genome Atlas and Gene Expression Omnibus. We assessed the m6A modification patterns of 664 bladder cancer samples based on 20 m6A regulators through unsupervised clustering analysis and systematically linked m6A modification patterns to TME cell infiltration characteristics. Gene ontology and gene set variation analyses were conducted to analyze the underlying mechanism based on the assessment of m6A methylation regulators. Principal component analysis was used to construct the m6Ascore to quantify m6A modification patterns of bladder cancer. Results: The genetic and expression alterations in m6A regulators were highly heterogeneous between normal and bladder tissues. Three m6A modification patterns were identified. The cell infiltration characteristics were highly consistent with the three immune phenotypes, including immune rejection, immune inflammation, and immune desert. The biological functions of three m6A modification patterns were different. Cox regression analyses revealed m6Ascore was an independent signature with which to assess patient prognosis (HR=1.198, 95%CI: 1.031–1.390). Patients with low-m6Ascore were characterized by increased tumor mutation burden, PD-L1 expression, and poorer survival. Patients in the low-m6Ascore group also showed significant immune responses and clinical benefits in CTLA-4 immunotherapy cohort (P =0.0069). Conclusions: The m6A methylation modification was related to the formation of TME heterogeneity and complexity. Assessing the m6A modification pattern of individual bladder cancer will improve the understanding of TME infiltration characteristics.